THE FACTORS OF AFFECTING GOVERNMENT PERFOMANCE AND ANALYSIS VALUE FOR MONEY APPROACH - Wahyu Cahyani Sekti; Suprihati Suprihati; Desy Nur Pratiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to determine the influence of fraud factors, GGG, OCB, and organizational culture on government performance as well as analysis of government performance using the value for money approach in regional work units Ngemplak District. Quantitative research with a population of 170. Taking the number of samples using the Slovin formula with an error limit of 5% obtained a sample size of 119. The research data used is primary data and secondary data. Data collection techniques use questionnaires and literature studies sourced from the 2019 and 2020 Boyolali Regency Government Agency Performance Reports. The data analysis method uses IBM SPSS version 25 as a test tool. Government Performance Analysis uses economic tests, efficiency tests and effectiveness tests. The results of this research show that the Fraud Factor has a significant positive effect on Government Performance, GGG has no significant effect on Government Performance, OCB has no significant effect on Government Performance, and Organizational Culture has a significant positive effect on Government Performance. And analysis of Government Performance using the Value For Money Approach has obtained results that are economical, quite efficient and very effective.